Sea level rise-induced habitat loss does not alter effective migration rate for the salt marsh insect Tumidagena minuta due to large genetic effective population size - Maguire, Billie; Tomasula, Jewel; Rippel, Tyler; Wimp, Gina M.; Hamilton, Matthew B. (Frontiers in Ecology and Evolution, 2023)
As anthropogenic change alters and fragments habitats, it is apparent that evolutionary change can co-occur with ecological change, though the scale and consequences of this contemporary evolution remain unclear. In coastal salt marshes of eastern North America, the flood tolerant low elevation marsh grass (Spartina alterniflora), is displacing Spartina patens, the flood intolerant high elevation marsh grass. Rising seas restrict S. patens, once occupying large areas of many hectares, to increasingly small fragments, some as small as a few square meters. Using nine microsatellite loci, we examined the genetic diversity and population structure of Tumidagena minuta, a minute, flightless planthopper and specialist herbivore of S. patens. We sampled T. minuta from S. patens habitat fragments of varying radius (3 - 82 meters) and distances (54 - 1,100 meters) to test how landscape variation affects population genetic parameters associated with microevolutionary processes. We sampled and genotyped 142 T. minuta individuals across six S. patens fragments in a single marsh in New Jersey, USA. We observed high polymorphism, observing between 7 and 28 alleles per locus and an average of 13.3 alleles per locus. We observed no genetic differentiation among sampled fragments (RST = -0.0109). The contemporary genetic effective population size (Ne) was estimated at approximately 360 (95% confidence interval: 208 - 1325) based on two-locus linkage disequilibrium. Based on an estimate of Nem = 32.4 in the finite island model, the estimated gene flow rate among these fragments was on the order of 10-2. These estimates, which are rarely produced for non-model insects, suggest that, despite rapid and precipitous decreases in habitat size and connectivity, T. minuta populations have remained large and have experienced little genetic differentiation due to drift. Ecological changes in fragment size and isolation at this scale have not influenced population genetic processes like effective migration rate for T. minuta, consistent with our expectations for an insect with a large population size.